Effect of onion meal and commercial prebiotic on growth and survival of common carp, Cyprinus carpio juveniles cultivated in earthen ponds - Taher , Majid (Iraqi Journal of Aquaculture, 2024)
The current experiment was conducted in earthen ponds at Agricultural Research Station belong to Aquaculture Unit- Agriculture College at Basrah University, Al-Hartha District from 16th May to 30th July 2022. Eight small earthen ponds (600 m2) were used for current experiment, and each pond stocked with 3000 common carp, Cyprinus carpio juveniles at average weight of 0.572 g. The purpose of current experiment is to investigate the differences in survival rate and growth performance with different additives [without additives (C), addition of 1.5 g probiotics/kg feed (T1), addition of 15 g dry onion meal/kg feed as prebiotic (T2), addition of 0.75 g probiotics and 7.5 g onion/kg feed as symbiotic (T3)]. The results revealed that survival rate for different treatments was more than 90%. Highest average final weight (13.58 g) and weight gain (13.01 g) were reached by fishes in T2. Statistical analysis of the results proved that there were no significant differences (P>0.05) in survival rate, growth criteria and feed conversion rate among different treatments. All treatments have a positive allometric growth pattern, with T2 exhibiting the maximum slope value (b) of 3.8097 and T1 exhibiting the lowest of 3.0421. Statistical analysis of condition factors proved that there were significant differences (P≤0.05) in modified condition factor between C and T2 with T1 and T3 and between T1 and T3. For relative condition factor there were significant differences (P≤0.05) between C and other treatments, while there were no significant differences (P>0.05) between T1, T2 and T3. The results of Fulton’s condition factor appeared significant differences (P≤0.05) between T2 and T3 with C and T1 and also between C and T1.